Screening of microbial consortium with high efficiency of lignin-degrading and its synergistic metabolic mechanism - Ru, Jinchuang; Jiang, Zhiyang; Li, Jiayu; Li, Xiang; Su, Zhencheng; Li, Tong; Xu, Mingkai (Frontiers in Microbiology, 2025)
IntroductionLignin is difficult to degrade, which makes its high-value utilization a challenge. So finding an efficient method to degrade lignin is very important. At present, microbial degradation is considered to be one of the most effective and environmentally friendly degradation methods that is widely accepted.MethodsThis study enriched three lignin-degrading microbial consortia R0, R1 and R2 using alkali lignin as the sole carbon source under 15 °C conditions. Using the methods of 16S rRNA sequencing, metagenomics, and metabolomics, the degradation mechanism of these three microbial consortia were systematically analyzed.ResultsThe microbial consortium R0, which has the best degradation efficiency, can degrade more than 80% within 6 days, with dominant genera being Achromobacter and Pseudomonas. The dominant genera in other two microbial consortia R1 and R2 are Pseudomonas and Achromobacter in R1, Pseudomonas and Sphingobacterium in R2. Protocatechuic acid is a central intermediate in the degradation of lignin, its degradation pathway was fully annotated in microbial consortia R0 and R1. Microbial consortium R0 has the most abundant of AA (Auxiliary Activities) family genes annotated as carbohydrate annotation enzymes. The dominant genera in the microbial consortium R0 based on AA family gene abundance were Pseudomonas and Achromobacter.DiscussionOur results indicated that Pseudomonas is the dominant genus in lignin degradation, the metabolic potential of other abundant genera suggests a possible complementary role in the lignin degradation process. In the lignin degradation system with Pseudomonas as the dominant genera, the degradation of protocatechuic acid is the core of the degradation process. This study could enrich the mechanism of efficient and stable lignin degradation by microbial consortium, and could provide theoretical guidance for the development of lignin biodegradation technology in industry.